Studies on the regulation of cellular activity and gene expression under acetaminophen intervention - Wang, Yue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This study investigated the effects of acetaminophen on the regulation of cellular activities and gene expression. Through a series of in vitro experiments, the effects of acetaminophen on cell proliferation, apoptosis and metabolism at different doses were analyzed and combined with gene expression profiling to reveal its regulatory mechanisms at the level of signaling pathways, transcription factor regulation and epigenetics. The results indicate that acetaminophen can significantly alter cell physiology and gene expression, suggesting its potential role and risk in drug intervention. This study provides new insights into the clinical application of acetaminophen and provides a theoretical basis for individualized therapy and drug optimization.